An Investigation into Membrane Technologies for the Removal of Microplastics from Municipal Wastewater Treatment Plant Effluents - LaRue, Ryan James (My University, 2023)
Microplastic (MP) pollution is ubiquitous in the aquatic environment. Though their properties are known to vary considerably, these particles are typically 1–5,000 μm in size and irregular in shape. Research suggests that MPs pose a significant hazard to aquatic ecosystems, lead to negative economic consequences, and may cause adverse human health effects. The effluents of municipal wastewater treatment plants (WWTPs) comprise a significant source of MPs, containing < 1 MP/L to > 440 MPs/L. Pursuant to the large volumes of wastewater processed, estimated daily effluxes can exceed one billion MPs/day in some WWTPs. Membrane technologies, like those used in some tertiary wastewater treatment applications, appear well-positioned to mitigate releases of MPs. However, research directly characterizing the performance of membranes in these applications is lacking. The studies in this work address this knowledge gap. To this end, irregularly-shaped MPs were produced in a novel milling/sieving process. Ultrafiltration and microfiltration membranes were challenged to these MPs suspended in secondary effluent wastewater to elucidate their fouling behaviour under realistic solution conditions. Subsequently, MPs milled/sieved from a fluorescently-labelled plastic feedstock were utilized in microfiltration experiments. Bulk MP concentrations in samples were easily measured using a plate reader to quantify MP rejection. Improving upon this technique, a new protocol involving a flow cytometer was developed, enabling the identification of individual fluorescent MPs in filtration samples, even when complex solutions chemistries were used. A culminating investigation was performed to bridge a gap in the literature between studies considering small-scale laboratory filtration phenomena and observations of large-scale WWTPs. Thus, the performance of a hollow fiber crossflow microfiltration module was evaluated in the filtration of wastewater containing MPs. Overall findings suggest that incidences of fouling by MPs can be managed via periodic cleaning processes, and the well-informed selection/operation of membrane technologies can contribute to high MP removal efficiencies (> 99%) in tertiary wastewater applications.
Keywords: microplastics; membranes; microfiltration; ultrafiltration; wastewater treatment